RESIDU INSEKTISIDA RUMAH TANGGA AEROSOL (Bahan aktif: Kelompok Pyrethroid) TERHADAP NYAMUK Culex quinquefasciatus DI LINGKUNGAN PEMUKIMAN KECAMATAN TINGKIR KOTA SALATIGA - , Lulus Susanti; , DR. Damar Tri Boewono, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: There are various selections of household insecticides. Aerosol is one of the various formulations of household insecticides has been used by the community.The active ingredients of household insecticide mostly pyrethroid group. Inappropriate method and dosage of use in the long run can accelerate the emergence of environmental pollution and resistance of insects against insecticide active ingredients. The majority of heterogenous community of Subdistrict of Tingkir at Salatiga Municipality have the habit of using mosquito repellent. So far socialization on appropriate method of using household insecticide has never been undertaken. Based on this condition the problem of the study is how community behaves in relation to the use of aerosol household insecticide and how is its impact against accumulative residue of insecticide active ingredients in cloth and susceptability of Culex quinquefasciatus from the location of the study against insecticide active ingredients. Objective: The study aimed to describe community behavior in the use of aerosol household insecticide and identify impact against accumulative residue of insecticide active ingredients in cloth and to the Cx.quinquefasciatus mosquitoes. Method: The study used descriptive analytical and quasi experimental method to identify community behavior and residue of pyrethroid active ingredients. Population of the study were community of Tingkir Subdistrict, Salatiga Municipality whereas samples were taken using quota sampling technique. Information on community behavior was obtained quantitatively and qualitatively. Measurement of insecticide residue was made to cotton cloth at respondents' bedroom using chromatography gas of the Ministry of Agriculture, Jakarta. Examination was also made to mosquitoes caught at the area of the study to identify susceptibility of Culex quinquefasciatus against insecticide active ingredients at the laboratory of Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit/B2P2VRP (Central Council of Vector and Disease Reservoir Research and Development). Result: Out of 161 users of mosquito repellent, 32.3% used aerosol. Knowledge of respondents was 57.2% inadequate